Subjective Outcome Evaluation of the Project P.A.T.H.S.: Findings Based on the Perspective of the Program Implementers (Secondary 1 Program) - Sandra K.M. Tsang; Eadaoin K.P. Hui; Daniel T.L. Shek; Bella C.M. Law (The Scientific World Journal)
The aim of the current study was to replicate the subjective outcome evaluation based on program implementers in the first year (2006/07 school year) of the Full Implementation Phase (Secondary 1 level) of the Project P.A.T.H.S. (Positive Adolescent Training through Holistic Social Programmes). After the completion of the Tier 1 program in the 2007/08 school year, 1324 implementers from 213 schools completed a Subjective Outcome Evaluation Form for instructors in order to assess their views of the program, themselves, and the perceived effectiveness of the program. Reliability test indicated the questionnaire was internally consistent. The results showed that, similar to the first year of implementation, high proportions of the respondents had positive perceptions of the program and their own performance. Regarding the perceived effectiveness of the program, roughly 90% of the respondents thought the program was helpful. A statistically significant increase in positive responses was also found in some items of perceived effectiveness in the second year of implementation. Possible factors contributing to such changes, including accumulation of experience and skill enhancement of the implementers, as well as stronger support from the schools, are discussed.